The Holy See and the repudiation of the doctrine of discovery between reductionism and denial of responsibility (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
Although the Vatican’s recent rejection of the doctrine of discovery is indeed welcome, its silence on any political responsibility for those 500-year-old papal bulls that authorized colonial powers to seize indigenous lands means that the battle is only half won. Worse still, the Vatican’s avoidance of any connection between the mass crimes endorsed against non-Christians and their consequences indicates that it is missing the point. As the bulls were issued by «representatives of God on Earth», such an implicit denial is a structural weakness that could hardly round off the «architecture of reconciliation» Pope Francesco is said to be aiming at. This essay aims to recall historical evidence of the Papacy’s direct and indirect responsibility while discussing the circumstances lying at the origins of the hierarchical organization of this world, which impacted not only the American but also the African continent, with permanent consequences for generations of its peoples and their descendants in the diaspora.
Keywords: Doctrine of discovery; Papacy; History of International Law; Human Rights; Colonialism; Autochthonous; Africa; Reparations